1994
DOI: 10.1007/bf00282755
|View full text |Cite
|
Sign up to set email alerts
|

The function of the hypusine-containing proteins of yeast and other eukaryotes is well conserved

Abstract: The hypusine-containing protein (Hypp) is highly conserved in evolution, from man to archaebacteria, but is not found in eubacteria. Hypp is essential for the viability for yeast cells, where two forms are encoded by the genes HYP1 and HYP2. The hypusine-containing protein Hyp2p, encoded by the HYP2 gene in yeast, is present under both aerobic and anaerobic conditions, whereas Hyp1p synthesis is restricted to anaerobiosis. hyp1 disruption mutants grown under anaerobic conditions reveal no detectable alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…It has already been shown that the eIF5A precursor protein isolated from a plant (i.e. alfalfa) can be activated by hypusine formation in yeast (35). The sequence of tobacco deoxyhypusine synthase shares all strictly conserved residues found in the primary structure of the enzymes from other sources (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…It has already been shown that the eIF5A precursor protein isolated from a plant (i.e. alfalfa) can be activated by hypusine formation in yeast (35). The sequence of tobacco deoxyhypusine synthase shares all strictly conserved residues found in the primary structure of the enzymes from other sources (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In the present EF-P crystal structure, the Arg-32 side chain protrudes toward the solvent at the end of the domain I arm. The bacterial EF-P reportedly lacks hypusine (13). Nevertheless, the conservation of the amino acid residues in the ␤3-␤4 connective linker and the basic residue at the tip of the loop implies the significance of this region for EF-P function.…”
Section: Structure Comparison Of Ef-p With Trna and Ribosome-binding mentioning
confidence: 99%
“…The enzyme that modifies lysine to hypusine in eIF-5A is essential for yeast viability (12). On the other hand, hypusine is not found in bacteria (13). The structures of eIF-5A from three Archaea, Methanococcus jannaschii, Pyrobaculum aerophilum, and Pyrococcus horikoshii, have two domains, which are composed of several ␤-strands (14)(15)(16).…”
mentioning
confidence: 99%
“…Even though the precise in vivo function of this protein is still unknown, hypusine formation in eIF-5A was shown to be central to cell viability [1][2][3].…”
Section: Introductionmentioning
confidence: 99%